2020
DOI: 10.3390/plants9111574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Contribution of Growth, Physiological, and Ionic Components Towards Salinity and Drought Stress Tolerance in Jatropha curcas

Abstract: Salinity and drought stress, singly or in combination, are major environmental menaces. Jatropha curcas L. is a biodiesel plant that can tolerate long periods of drought. However, the growth performance and stress tolerance based on physical, chemical, and physiological attributes of this plant have not yet been studied. To address this question, J. curcas seedlings were grown in a completely randomized design in plastic pots filled with soil to evaluate the effects of salinity and drought stresses on growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 67 publications
5
42
0
Order By: Relevance
“…In the present study, MSI changed modestly when plants were exposed to salinity stresses relative to control conditions (Table 2). Our results validate that these traits can be the major attributes inducing towards salt tolerance, because these were less affected by salinity stress (Abrar et al 2020). Moreover, a strong correlation was observed between these physiological parameters (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In the present study, MSI changed modestly when plants were exposed to salinity stresses relative to control conditions (Table 2). Our results validate that these traits can be the major attributes inducing towards salt tolerance, because these were less affected by salinity stress (Abrar et al 2020). Moreover, a strong correlation was observed between these physiological parameters (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…However, this result is inconsistent with other reports, which have shown that salinity stress can significantly reduce the intercellular water status in plants (Qin et al 2010). The membrane stability index (MSI) is another physiological indicator that widely used to estimate potential salinity tolerance in different crops (ElBasyoni et al 2017;Abrar et al 2020;Ebrahim et al 2020). It has been reported that MSI is more effective in screening tolerant genotypes at the early growth stage (Farooq and Azam 2006), since it often affected by lipid peroxidation caused by oxidative stress that results in the production of malondialdehyde (MDA) (Ahmed et al 2013).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Chlorophyll content had a positive relationship with the rate of photosynthesis (Yeganehpoor et al 2016). According to some researchers, the change of chlorophyll content in leaves was one of plant response to drought, to minimize light absorption by chloroplasts (Anjum et al 2011;Ucar et al 2018;Abrar et al 2020). In addition, the other research stated that chlorophyll content changed can be also caused by increased environmental pressure, especially and salinity (Taïbi et al 2016;Bertoldo et al 2018;.…”
Section: Discussionmentioning
confidence: 99%